The Main Forest Pests and Diseases in U.S.S.R. and the Methods of their Control - Nair, P. N. (Indian Forester, 1966)
The forcsts in U.S.S.R. are subject to considerable damage caused by a variety of insect pests and disease causing organisms. Some of them are more or less specific in their choice of hosts and the other ecological conditions, whereas the others are not so specific. The intensity of damage also depends on the environmental conditions, the worst being in a set of conditions in which the pests or the pathogen can multiply profusely. Various control measures have been devised to protect the forests from pests and diseases. The main principle of forest protection lies in keeping the forests in proper sanitary conditions and applying timely measures for the prevention or destruction of pests and diseases. Generally, prophylatic prescriptions aimed at preventing, the outbreak of injurious insects and diseases in forests are made in the plans drawn out for the management of the forests. The sanitary maintenance of the forests is a State responsibility and is regulated by Enactments. The control methods can generally be classified as silvicultural, biological and chemical. Chemical control measures are commonly resorted to in Russian Forestry. The application of the chemical is either by dusting or spraying. Various devices have been made to make the chemical treatment effective 3nd economical. Both aerial and ground applications are made either alone or in combination, depending on the terrain of the forest area, its extent and the nature of pest damage. Special machines, known as aerosol generators, which are used for treatment from ground, are particularly effective in small areas. The spray chat results from this device is in the form of mist thereby enhancing the coverage . The aim of this article is to give a brief and general account of the main pests and diseases that are economically important in U.S.S.R. forestry and the principles and methods of their control. Latest developments: in this field are briefly described.